Third preliminary report of the Danish archaeological excavations at Panayia Ematousa, Aradippou, Cyprus - Sørensen, Lone Wriedt; Destrooper-Georgiades, Anne; Frederiksen, Rune; Winther Jacobsen, Kristina; Lund, John (Proceedings of the Danish Institute at Athens, 1998)
N/A